Toxicity evaluation of gold nanoparticles using an Allium cepa bioassay. Issue 29 (1st March 2016) - Rajeshwari, A.; Suresh, S.; Chandrasekaran, Natarajan; Mukherjee, Amitava
Abstract : The size- and dose-dependent cytogenetic effects of gold NPs were evaluated for the first time by a simple and cost-effective Allium cepa ( A. cepa ) bioassay. Abstract : The progressive increase in the usage of gold nanoparticles (NPs) in industrial and commercial products leads to the potential release of nanoparticles into the environment, which could cause adverse effects on living systems. In the present work, the size- and dose-dependent cytogenetic effects of gold NPs towards a plant system were evaluated for the first time by a simple and cost-effective Allium cepa ( A. cepa ) bioassay. Citrate-capped gold NPs of three different sizes, 15 (Au15), 30 (Au30), and 40 (Au40) nm, were synthesized by a citrate reduction method. The mean hydrodynamic diameter and morphology of as-synthesized gold NPs were characterized by dynamic light scattering and transmission electron microscopy analyses. Several chromosomal aberrations were observed under an optical microscope upon the exposure of A. cepa root tip cells with 0.1, 1, and 10 μg mL −1 of Au15, Au30, and Au40. The mitotic indices in treated root tips were directly proportional to the NP concentration and inversely related to their size. The vehicle control (citrate) had no impact on the mitotic index. Furthermore, the effects of gold NPs on the A. cepa root tip were confirmed by analyzing the generation of various reactive oxidant species (hydroxyl, superoxide and hydrogen peroxide), which possibly led to lipid peroxidation in the system.